Emotional Triggers and Self-Control in Digital Consumption within Islamic Communities - Riska Amelia; Muhammad Yafiz; Kamilah Kamilah (Celebes Scholar pg, 2025)
This study explores the psychological and spiritual dynamics underlying impulsive buying behavior within Islamic educational communities, focusing on how emotional triggers interact with financial literacy, platform trust, lifestyle orientation, and the use of financial technology. Drawing from a sample of teachers and staff in two pesantren in North Sumatra, the research applies Partial Least Squares Structural Equation Modeling to test a model that includes fear of missing out as a key emotional predictor, and self-control as both a direct influence and a moderating mechanism. The findings reveal that among all variables tested, only fear of missing out exerts a statistically significant effect on impulsive buying. Other factors such as Islamic financial literacy, fintech usage, trust, and lifestyle show no direct influence, highlighting the limited behavioral power of cognitive or infrastructural preparedness when emotional pressure dominates the decision-making process. Self-control emerges as a critical behavioral firewall, directly reducing impulsive tendencies and weakening the emotional force of fear of missing out. These results underscore a growing behavioral dissonance between ethical intention and digital action. They suggest that Islamic financial education must evolve beyond informational delivery to include the cultivation of emotional regulation, ethical habit, and behavioral resilience. In a commerce environment increasingly governed by acceleration and visibility, the preservation of Sharia-compliant financial behavior will depend less on what individuals know and more on how they manage what they feel and how they pause before they act.